Jasmonic acid treatment alleviates chilling injury in peach fruit by promoting sugar and ethylene metabolism. (15th February 2021) - Zhao, Yaoyao; Song, Congcong; Brummell, David A.; Qi, Shuning; Lin, Qiong; Duan, Yuquan
Highlights: Jasmonic acid signals via ethylene and sugars to control chilling injury in peach fruit. Jasmonic acid promotes production of ethylene via increased abundance of ACS1 Mrna. Jasmonic acid treatment maintains the soluble sugar content of cold-stored peaches. Abstract: Peach ( Prunus persica L.) fruit are highly susceptible to chilling injury during cold storage, resulting in internal flesh browning and a failure to soften normally. We have examined the effect of a postharvest treatment consisting of a brief (30 s) dip in the natural plant hormone jasmonic acid, prior to storage at 4 °C. Jasmonic acid treatment reduced the severity of internal flesh browning and did not inhibit fruit softening over a 35 d storage period. Two major physiological effects of jasmonic acid on the fruit were observed, an increase in ethylene production and a prevention of the decline in soluble sugar content seen in controls. An increased soluble sugar content may have multiple benefits in resisting chilling stress, scavenging reactive oxygen species and acting to stabilize membranes. Our results show that a treatment with jasmonic acid can enhance chilling tolerance of peach fruit by regulating ethylene and sugar metabolism.